Can tendon reflexes be elicited by both stretch and vibration in man?. Issue 7 (27th May 2021) - Tfelt‐Hansen, Peer; Meritam Larsen, Pirgit; van Deurs, Ulla; Fabricius, Martin
Abstract: Aim of study: When the biceps tendon is tapped, a contraction is elicited in the biceps muscle. This also occurs with tapping of the radial bone, and it has been suggested that vibration is a stimulus for deep tendon reflexes. We investigated whether the normal stimulus for the deep tendon reflex is a sudden stretch, a phasic vibration, or both. Furthermore, we investigated the importance of forearm position for the reflex response in controls and stroke patients. Methods: We investigated 50 neurological outpatients without clinical signs of neurological disorders in the arms. The biceps tendon and distal radius were tapped with the forearm in the midway (90°), supinated, and pronated positions. In 10 of these patients, the two reflexes were also investigated with quantitative electromyography (EMG) measurements in the 3 positions. Another 10 patients were investigated clinically when stretch of elbow was eliminated and 17 patients were examined when prestretching of the biceps tendon was avoided. Finally, we examined 32 patients that had experienced stroke. Results: In 94% (47/50) of patients, after a radial tap, the biceps contraction disappeared in the supinated forearm, and the median peak‐to‐peak amplitude of the surface EMG response ( n  = 10) decreased from 1.1 to 0.2 mV ( p  < .01). Elimination of elbow stretch as well as pressure on the biceps tendon did not change the reflex response. In 84% (27/32) of stroke patients, after a radial tap, the biceps contraction persisted in supination in the arm with hyperreflexia. Conclusion: The combined clinical and EMG results are consistent with the concept that the deep tendon reflexes in man can be elicited by both stretch and phasic vibration. Clinicians should be aware that the brachioradial reflex depends on the forearm position. Abstract : Human reflexes; Position of upper limb; Stroke.